Investigating the use of solid waste as alternative fuels in Egypt - Shahat, Fatma Adel (AUC Knowledge Fountain, 2016)
Every year Egypt produces enormous amounts of solid waste that reached 89 million tons/year in 2012 and still in continuous increase. As most experts agree, waste can be a hidden treasure for the nation, if it is fully exploited. Indeed, solid waste can be reused, recycled, or even recovered as a source of energy instead of simply being disposed in dumpsters and landfills. Given the need for alternative sources of energy, energy crisis, and waste management problems in Egypt, waste-to-energy (WTE) seems to be an optimum solution for both problems: energy and waste disposal. In the first phase of this research, a comparative study was conducted to investigate the average calorific value of various waste materials from agricultural, industrial, and municipal waste sources including six types of plastics, tires, sawdust, rice straw, rice husk, corn husk, bagasse, and onion leaves. Due to the fact that biomass pellets are more uniform, and easier to transport and store, the second phase of the study investigated the use of starch, water, and Ca(OH)2 as binders for biomass pellets and their impact on the average calorific value. The final phase investigated the emissions produced from the most promising waste materials. The results showed that among the six types of plastics, polypropylene (PP) has given the highest average calorific value, while bagasse had a maximum average calorific value among the five investigated agricultural wastes. Rice straw can also be one of the promising agricultural WTE materials in Egypt because it is abundant in large quantities; same as tires which are widely available and have high average calorific value when compared to fossil fuels like coal and diesel. From the second phase, the utilization of starch, water, and Ca(OH)2 had a minor impact on the average calorific value of the investigated biomass with a maximum decrease of 10% of the original calorific value, however, this percentage changed from one material to another. In the third phase, emissions measured were CO, NO, NO2, CO2, and SO2 for rice straw, bagasse, tires, and polypropylene, which were selected based on the first phase results. Emissions were measured using Testo gas analyzer that only provided rough estimation of emissions and only comparative figures. The results showed that tires had the highest mass of SO2, CO, and CO2 per unit mass of tires, while bagasse had the maximum NO value. NO2 was almost the same for tires and bagasse, and they gave the highest value of NO2. However, the produced emissions could have been impacted with the percentage of mass loss in the combustion process, and other pollutants that could not be measured in this study. The results obtained can be used for industrial application, especially for energy-intensive sectors that can use waste as a source of energy because it includes the average calorific values of different materials, which is one of the most important factors that should be taken into consideration while evaluating WTE materials, as well as the produced emissions from the most promising ones. Determining these emissions would help those industries to decide on mitigation and removal technologies that can be used in order to reduce those emissions.